Lossless multi-channel audio codec - FEJZO, ZORAN (2016)
A multi-channel audio encoder for coding a digital audio signal sampled at a known sampling rate and having an audio bandwidth and blocked into a sequence of frames is provided and comprises: a core encoder (404) that extracts and codes a core signal from the digital audio signal into core bits; a packer that packs the core bits plus header information into a first bitstream; a core decoder (412) that decodes the core bits to form a reconstructed core signal; a summing node (420) that forms a difference signal from the reconstructed core signal and the digital audio signal for each of the multiple audio channels; a lossless encoder (424) that segments each frame of the multi-channel difference signals into a plurality of segments and entropy codes the segments into extension bits, said lossless encoder selecting a segment duration to reduce an encoded payload of the difference signals in the frame subject to a constraint that each segment must be fully decodable and less than a maximum size; and a packer (410) that packs the extension bits into a second bitstream.